Experimental Study of a Multispectral Piston Sensing Technology - Li Dong; Haotong Ma; Qi Peng; Ge Ren; Bo Qi; Shanchao Liu; Zongliang Xie (IEEE Photonics Journal)
Nowadays giant segmented telescopes and multiaperture telescopes have grown out of the quest for high-resolution observations in astronomy. One of the major issues is the phasing of such telescopes. A concept of multispectral piston sensing technology is, therefore, re-examined and studied experimentally for the first time. Based on the phase-shifting “Telescope-Interferometer” technology and multispectral information, the multispectral piston sensing technology was assumed to be feasible with the segmented telescopes and multiaperture telescopes. In this paper, the optical scheme for this method has been designed and realized. Experimental tests have been carried out and demonstrated that the method is effective for piston sensing in a large capture range with high-precision despite some instrument-related limitations that can be eliminated. In our tests, the shortest coherent length of the three working spectrums we chose was less than 17.5 μm. Results show that the method successfully handled an amplitude of correction of about ±8 μm with an accuracy of about λ/30 (λ = 535 nm) RMS in our tests, and we can foresee that the capture range can be enlarged if we choose working spectrums with larger coherent lengths.